OPTIMAL PARTICLE SIZE DEFINITION DURING COOPERATIVE EXTRACTING OF DIFFERENT TYPES OF HERBAL RAW MATERIALS WHICH COMPRISE INTO INFUSION COMPOSITION «VENETON» - S. A. Kutsenko; O. V. Kutovaya; O. A. Ruban; I. V. Kovalevskaya (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
According to previously carried out research of pharmaco-technological characteristics establishment of every herbal raw material it has been defined that herbal collection includes herbal raw material of different anatomo-morphological structure. It can be reflected in the dynamics of its extraction. As a result the raw material which is completely exhausted will be saved in the extractor as ballast and the duration of the process will depend on the raw material which is extracting more slowly. It is supposed that the main factor to solve the problem of different kinds of herbal raw materials combined extraction will be particle dispersity. Reducement of fragments, external power action (mixing), time, temperature, extragent volume, phase contact surface, raw material and extragent correlation, kind of extragent play the main part here.